2017
DOI: 10.1021/acsinfecdis.7b00095
|View full text |Cite
|
Sign up to set email alerts
|

Attaching the NorA Efflux Pump Inhibitor INF55 to Methylene Blue Enhances Antimicrobial Photodynamic Inactivation of Methicillin-Resistant Staphylococcus aureus in Vitro and in Vivo

Abstract: Antimicrobial photodynamic inactivation (aPDI) uses photosensitizers (PSs) and harmless visible light to generate reactive oxygen species (ROS) and kill microbes. Multidrug efflux systems can moderate the phototoxic effects of PSs by expelling the compounds from cells. We hypothesized that increasing intracellular concentrations of PSs by inhibiting efflux with a covalently attached efflux pump inhibitor (EPI) would enhance bacterial cell phototoxicity and reduce exposure of neighboring host cells to damaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 61 publications
0
43
0
Order By: Relevance
“…Similarly, an in vitro study demonstrated that verapamil, an efflux pump inhibitor, when combined with aPDT, required a lower light dose for effective antibacterial, and antibiofilm action against S. aureus (de Aguiar Coletti et al, 2017). In further development of such an approach, it was recently demonstrated that INF55-(Ac)en–MB, synthetic antimicrobial hybrids designed by covalently linking a PS (methylene blue) to efflux pump inhibitors (INF55 and INF271) were more effective in treating wound infections caused by S. aureus or A. baumannii studied in mice models (Rineh et al, 2017, 2018).…”
Section: Photodynamic Light Therapymentioning
confidence: 99%
“…Similarly, an in vitro study demonstrated that verapamil, an efflux pump inhibitor, when combined with aPDT, required a lower light dose for effective antibacterial, and antibiofilm action against S. aureus (de Aguiar Coletti et al, 2017). In further development of such an approach, it was recently demonstrated that INF55-(Ac)en–MB, synthetic antimicrobial hybrids designed by covalently linking a PS (methylene blue) to efflux pump inhibitors (INF55 and INF271) were more effective in treating wound infections caused by S. aureus or A. baumannii studied in mice models (Rineh et al, 2017, 2018).…”
Section: Photodynamic Light Therapymentioning
confidence: 99%
“…Bioluminescence combined with a totally implantable venous access port model has been used to assess localized and systemic infections related to CVC in rats, reproducing clinically significant situations of foreign body-associated infections (351). These models have been valuable in the investigation of aPDT, which involves photosensitizing dyes topically applied to the infection site and subsequent harmless visible light illumination and reactive oxygen species (ROS) generation (324,376). Bioluminescence imaging of localized infections not only is well suited for monitoring the effectiveness of experimental antimicrobial therapeutics but also has a major role in the study of microbial virulence and pathogenicity.…”
Section: In Vivo Imaging Toolsmentioning
confidence: 99%
“…While some studies had found that the reference strain ATCC 25922 was slightly more susceptible to photoinactivation than multidrug resistant clinical isolates [21,31], our results show that this is the case only for a few isolates (strains 11, 13, and 24), while the majority are significantly more susceptible (Figure 1). Since MB is internalized by E. coli [32,33] and is known to be a substrate for efflux pumps in E. coli as well as in other bacteria [19,34,35], one could reasonably expect some tolerance to aPDT in the resistant strains. We can speculate that resistance mechanisms such as reduced permeability to antimicrobial agents, active efflux of the antimicrobial from the cell, enzymatic alterations, or degradation of the antimicrobial agent [36] may contribute to modulate the photodynamic activity of MB, but they are not determinants for aPDT efficiency.…”
Section: Discussionmentioning
confidence: 99%